Perbandingan Bakteriologi Escherichia Coli Pada Sumber Air Minum Sumur Gali Dengan Sumber Air Minum Sumur Bor Di Terminal Tirtonadi Surakarta - Ramadhan, Alban; , Prof.Dr.J.Priyanbodo,dr.,MS.,Sp.MK (k) (2016)
Background : Dug well and drilling well still used as a source of widely drinking water. Both wells are still used in Terminal Tirtonadi. For that to know whether the quality of the source water from wells drilled with wells meet drinking water standards Objective: Knowing the difference in the quality of the source water from wells dug artesian well water sources . Escherichia coli is used as an indicator of pollution of water sources. Methods : This was a cross-sectional observational study. Sampling was conducted in January 2016 in wells around Terminal Tirtonadi Surakarta. Mechanical sampling with purposive random sampling method obtained 12 samples consisting of 6 samples dug wells and 6 samples wellbore . A study of the samples was performed using methods Most Probable Number(MPN) equipped with a complete test to identify the type of bacteria in the samples and cultivation on an agar medium and performed biochemical tests. Results : The study shows that there are differences in water quality in drilled and dug wells , boreholes have a better quality compared to the dug this is proved by statistical analysis using the Mann Whitney test with values ( p≤ 0.05 ).